The secret garden - Burnett, Frances Hodgson, 1849-1924.; Martin, Ann M., 1955- (New York : Scholastic, Inc., 1999)
Ten-year-old Mary comes to live in a lonely house on the Yorkshire moors and discovers an invalid cousin and the mysteries of a locked garden.
Included in Oprah's Book Club Kids Reading List.
6.7
5-8.
970
Accelerated Reader AR
Keywords: Orphans -- Juvenile fiction; People with disabilities -- Juvenile fiction; Friendship -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Gardens -- Juvenile fiction; Yorkshire (England) -- Juvenile fiction; Fiction